Promoter Region and Regulatory Elements of IGF and VIP Genes Associated With Reproductive Traits in Chicken - Bosenu Abera; Hunduma Dinka; Hailu Dadi; Habtamu Abera (International Journal of Genomics)
This study investigates the promoter region and regulatory elements of chicken insulin-like growth factor (IGF) and vasoactive intestinal polypeptide (VIP) genes associated with reproductive traits. Several in silico tools, such as Neural Network Promoter Prediction (NNPP), Multiple Expectation maximizations for Motif Elicitation (MEME-Suite), GC-Profiles, microsatellite prediction (MISA-web), CLC Genomics, Multiple Association Network Integration Algorithm (GeneMANIA), and Gene Ontology for Motifs (GOMO), were used to characterize the promoter regions and regulatory elements of IGF and VIP genes. The in silico analysis showed that the highest promoter prediction scores (1.0) for TSS were obtained for three gene sequences (IGFP4, VIP, and VIPR1), while the lowest promoter prediction score (0.8) was obtained for IGF1. The present analysis revealed that the best common motif, Motif II, resembles three major transcription factor families: zinc finger family, homeobox transcription factor family, and high-mobility group factor family, accounting for about 79.17%. This study found that 62.5% of the candidate transcription factors have interaction with the Wnt signalling pathway to regulate transcription. Key regulatory elements identified in this study, such as CPEB1, MAFB, SOX15, TCF7L2, TCF3, and TCF7, play critical roles in activating and repressing transcription, with significant implications for embryonic and nervous system development. In the current study, very rich CpG islands were identified in the gene body and promoter regions of IGF and VIP genes. Generally, in silico analysis of gene promoter regions and regulatory elements in IGF and VIP genes can be helpful for comprehending regulatory networks and gene expression patterns in promoter regions, which will guide new experimental studies in gene expression assays.